Pre-election polling and the democratic veneer in a hybrid regime. Issue 5 (3rd July 2020) - Conduit, Dara; Akbarzadeh, Shahram
ABSTRACT: Hybrid regimes have consolidated on the back of techniques that balance strong regime structures with tokenistic pluralism. This democratic veneer is performed through pseudo markers of democracy such as weak political parties and semi-competitive elections, which aim to ratify regime legitimacy. How public opinion polling fits into authoritarian landscapes, however, is an aspect of hybrid regimes that remains less understood. Scholars of public opinion research in democracies believe that polling can contribute to constructing the world around it, prompting this paper to examine whether public opinion research – and pre-election polling in particular – contributes to the democratic veneer in hybrid regimes by constructing a perception of participatory democracy. It examines the nature and quality of pre-election polling undertaken in authoritarian Iran in the lead-up to the 2017 presidential election in order to make preliminary observations about the potential impact of polling on a regime's pluralist credentials. It finds that while most polls were poor quality, no polling in an authoritarian environment is benign because the very process of asking citizens their opinions and publicizing responses creates an impression that individual opinions count, in an environment where the opposite is often true.